Re-imagining indigenous knowledge and practices in 21st century Africa : debunking myths & misconceptions for conviviality and sustainability - Muyambo, Tenson; Hlatywayo, Anniegrace M.; Sithole, Pindai M.; Mawere, Munyaradzi (Langaa RPCIG, 2022)
This book is on the re-imagination of Indigenous Knowledge Systems (IKS) and practices in 21st century Africa.